Study on the Students' Perception of Knowledge Usefulness and Necessity Concerning Tourists' Protection - Valentin Niţă; Gina Ionela Butnaru (Amfiteatru Economic Journal, 2010)
The subject concerning the protection of the consumers' rights and interests is of high concern nowadays, because the market economy, by its mechanisms and by the principles it promotes is permanently associated with the notion of correctness. Considering the consumer's needs, the notion of correctness from the market economy has in view the assurance of great informative possibilities, of choosing and buying the products at convenient prices, with a corresponding quality. The market should be transparent, the information should circulate freely, and the prices should be known. Consequently, the competition will be efficient, loyal, and beneficial for the consumer. Taking into account that one fundamental right of the consumer is to be informed and educated, we intend to realize a study on the identification and solving of the problems met by the students from the departments of Tourism Geography and Environmental Geography, concerning the usefulness and the necessity of a knowledge regarding the protection of tourism consumers. In correlation with this objective, we consider that the academic environment in which the students develop themselves represents an opportunity in what concerns sending and accumulating information from different fields, to efficiently contribute to the formation of a citizen who is aware of his rights as a consumer.
Keywords: C01; C12; D18; 330; consumers' protection; tourism; problem identification; students